The role of blended learning in improving medical students’ academic performance: evidence from Pakistan - Ashraf, Muhammad Azeem; Tsegay, Samson Maekele; Gull, Nida; Saeed, Muneeba; Dawood, Hussain (Frontiers in Medicine, 2024)
ObjectiveThe study examines the role of blended learning in improving medical students’ academic performance through self-regulatory learning and technological competence and identifies the moderating role of perceived institutional support in the relationships between self-regulatory learning, perceived teacher credibility, technological competencies, and academic performance.MethodsThe study was based on behavioral learning theory as a theoretical framework, and an adapted questionnaire was used to collect the data. In total, 275 medical students participated in the study, and the data was analyzed using structural equation modeling techniques with SmartPLS.ResultsThe results indicate that self-regulatory learning significantly affects student academic performance and mediates the role of teachers’ credibility and technological competencies. Furthermore, perceived institutional support is a significant moderator in the relationship between self-regulated learning, technological competencies, and teacher credibility.ConclusionThe study highlights the importance of self-regulated learning in students’ academic achievement. Moreover, it suggests that educational institutions should advance teachers’ competence and encourage collaborative learning to enhance students’ learning, motivation, and academic performance.